WTO, Negara Sedang Berkembang dan Gerakan Masyarakat Sipil Global - Winanti, Poppy Sulistyaning (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
This article aims at addressing the question on the role of global civil society movement and its significance to the WTO and developing countries. The WTO has been critized as the Rich Mans Club since it primarily serves the benefits of developed countries. The emergence of global civil society movement can be considered as the opportunity to diminish the undesirable effects of the existing trading order. However, the findings show that despite the rapid growth of such a movement, their agendas do not always correspond to the developing countries needs. Some facts even demonstrate that sometimes their activities are conflicting with developing countries main interests.